A CHRISTIAN READING OF PATAÑJALI’S YOGA-SŪTRA - Kochumuttom, Thomas (Journal of Dharma, 2010)
The classical text of yoga is Yoga-sūtra (YS) written by Patañjali in early Christian centuries. The theory and practice of yoga were certainly there even before him, who then systematically presented them. The book written in the form of short statements called sūtras has four parts entitled: samaadhi, saadhana, vibhūti and kaivalya. They deal respectively with the concentration of mind which is the trait of a yogi, the practices leading to it, the extraordinary endowments of a yogi, and the final state of liberation.